Maternal clinical profile and immediate neonatal outcome in term large for gestational age neonates - Jena, Pravati; Panda, Santosh K.; Nayak, Manas; Rath, Soumini; Pradhan, Deepti D. (International Journal Of Community Medicine And Public Health, 2019)
Background: The objective of the study was to know the maternal clinical profile and short term outcome of term large-for-gestational-age (LGA) neonates. Methods: The study was a prospective observational study conducted in the tertiary neonatal unit, Odisha, during the study period February to November 2018. All inborn term neonates with birth weight above 90th percentile for gestational age excluding neonates with major congenital anomalies were included. Maternal clinical profile data from the antenatal records, neonatal demographic profile and co-morbidities over time were recorded using a checklist. The analysis of data was done using SPSS 21.0. Univariate summary statistics and bivariate Fischer’s exact test were used to analyse the data. Results: The prevalence of delivery of LGA and macrosomic neonate in our institution was 2.5%, and 1.1% respectively. Ninety one percent of LGA neonates were born before 39weeks and 80% babies delivered by cesarean section. Majority 39 (86.7%) of LGA babies were born to non-diabetic mother, four (8.9%) neonates born to GDM mother, two (4.4%) were born to mother with pre pregnancy diabetes mellitus. Sixteen (35.5%) neonates were admitted to NICU for different comorbidities like neonatal jaundice (37.8%), polycythemia (24.4%), transient tachypnea of new-born (20%), hypoglycemia (15.6%), hypocalcaemia (15.6%), and seizure (4.4%). The comorbidities like hypoglycaemia, hypocalcemia, respiratory distress were more in LGA babies with diabetic mother compared to non-diabetic mother. Conclusions: About nine in ten LGA neonates were born to non-diabetic mothers, however, LGA infants of diabetic mothers are at higher risk of metabolic complications like hypoglycemia, hypocalcemia compared to non-diabetic mother.